Health-Related Quality of Life and Self-Care Management Among People With Diabetic Foot Ulcers in Northern Thailand - Saneh Khunkaew RNMSc; Ritin Fernandez RNMSNPhD; Jenny Sim RNBAppSc (Nursing) (SAGE Publishing, 2019)
Diabetic foot ulcers (DFUs) are a common complication of diabetes that impacts on the health-related quality of life (HRQOL). Foot care is an important factor in the self-care management of patients with DFUs. The objective of this study was to investigate the HRQOL and foot care management of people with DFUs. A cross-sectional study involving 41 people with DFUs was conducted at a large tertiary hospital in Northern Thailand. The Diabetic Foot Ulcer Scale-Short Form and the VA-Diabetes Foot Care Survey were used to assess the HRQOL and foot care management among people with DFUs. The majority of the participants were female ( n  = 24, 58.5%), and the mean age was 62.13 years. The scores for HRQOL in the six domains were as follows: leisure (66.95 ± 28.03), physical health (68.93 ± 28.51), dependence or daily life (80.08 ± 25.23), negative emotions (71.23 ± 29.48), worried about ulcers (62.20 ± 31.97), and bothered by ulcer care (69.36 ± 25.20). High scores indicate a high (good) HRQOL. Less than a third of the participants reported that they had received education about foot care management. Almost all participants reported that they washed their feet daily; however, a large proportion did not test the water temperature or use lubricants on their feet. Most of the participants did not have a mirror for checking under their feet (48.8%), and there was a lack of knowledge about how to use a mirror for foot inspections (51.2%). This study provides guidance for clinicians on the content and delivery of diabetes education programs for people with diabetes (and DFUs) in Northern Thailand. The findings provide guidance on existing knowledge and the need for programs to address barriers to foot self-care management both in terms of skills and attitudes.